Triterpenoids Extracted From Antrodia cinnamomea Mycelia Attenuate Acute Alcohol-Induced Liver Injury in C57BL/6 Mice via Suppression Inflammatory Response - Liu, Yange; Wang, Zhuqian; Kong, Fange; Teng, Lesheng; Zheng, Xiaoyi; Liu, Xingkai; Wang, Di (Frontiers in Microbiology, 2020)
Excessive alcohol consumption causes liver injury–induced mortality. Here we systematically analyzed the structure of triterpenoids extracted from Antrodia cinnamomea mycelia (ACT) and investigated their protective effects against acute alcohol-induced liver injury in mice. Liquid chromatography–mass spectrometry and liquid chromatography with tandem mass spectrometry were performed to determine the structures of ACT constituents. Alcohol-induced liver injury was generated in C57BL/6 mice by oral gavage of 13 g/kg white spirit (a wine at 56% ABV). Mice were treated with either silibinin or ACT for 2 weeks. Liver injury markers and pathological signaling were then quantified with enzyme-linked immunosorbent assays, antibody array assays, and Western blots, and pathological examinations were performed using hematoxylin-eosin staining and periodic acid–Schiff staining. Triterpenoids extracted from A. cinnamomea mycelia contain 25 types of triterpenoid compounds. A 2-weeks alcohol consumption treatment caused significant weight loss, liver dyslipidemia, and elevation of alanine aminotransferase, aspartate aminotransferase, γ-glutamyl transferase, and alkaline phosphatase activities in the serum and/or liver. These effects were markedly reversed after 2-weeks ACT administration. Triterpenoids extracted from A. cinnamomea mycelia alleviated the organ structural changes and inflammatory infiltration of alcohol-damaged tissues. Triterpenoids extracted from A. cinnamomea mycelia inhibited proinflammatory cytokine levels and enhanced anti-inflammatory cytokine levels. Acute alcohol treatment promoted inflammation with significant correlations to hypoxia-inducible factor 1α (HIF-1α), which was reduced by ACT and was partially related to modulation of the protein kinase B (Akt)/70-kDa ribosomal protein S6 kinase phosphorylation (p70S6K) and Wnt/β-catenin signaling pathways. In conclusion, ACT protected against acute alcohol-induced liver damage in mice mainly through its suppression of the inflammatory response, which may be related to HIF-1α signaling.